(3GdYbjOI GdeajOIs - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdChMO ehab GdOjf CHh eMeO YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdebOSi QMeg Gddg GdMeO ddg GdeMehO Hcd dSGf GdeYHhO ai cd ReGf GdPi dGjNdh ef Ydeg ecGf s
(3BNQgG (B:s
(3hCeG GdSfI GdJi gi EeGe aQhY GdOjf cGdWhGFa GdCQHYI hGdMeO ddg QH GdYGdejf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds